Geometric morphometric analysis of the effect of temperature on wing size and shape in Aedes albopictus - T. Phanitchat (2020)
© 2019 The Royal Entomological Society Wing geometry helps to identify mosquito species, even cryptic ones. On the other hand, temperature has a well-known effect on insect metric properties. Can such effects blur the taxonomic signal embedded in the wing? Two strains of Aedes albopictus (laboratory and field strain) were examined under three different rearing temperatures (26, 30 and 33 °C) using landmark- and outline-based morphometric approaches. The wings of each experimental line were compared with Aedes aegypti. Both approaches indicated similar associations between wing size and temperature. For the laboratory strain, the wing size significantly decreased as the temperature increased. For the field strain, the largest wings were observed at the intermediate temperature. The two morphometric approaches describing shape showed different sensibilities to temperature. For both strains and sexes, the landmark-based approach disclosed significant wing shape changes with temperature changes. The outline-based approach showed lesser effects, detecting significant changes only in laboratory females and in field males. Despite the size and shape changes induced by temperature, the two strains of Ae. albopictus were always distinguished from Ae. aegypti. The present study confirms the lability of size. However, it also suggests that, despite environmentally-induced variation, the architecture of the wing still provides a strong taxonomic signal.